2002
DOI: 10.1007/s00204-002-0363-5
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural changes related to olfactory mucosal metaplasia and bulbar glial fibrillary acidic protein (GFAP) induction in methylsulphonyl-dichlorobenzene-treated mice

Abstract: Methylsulphonyl-2,6-dichlorobenzene [2,6-(diCl-MeSO(2)-B)], and its 2,5-chlorinated isomer [2,5-(diCl-MeSO(2)-B)] bind firmly in the olfactory mucosa of mice. Both isomers are also selectively localised in the olfactory bulb. Persistent olfactory mucosal metaplasia is induced by 2,6-(diCl-MeSO(2)-B) whereas 2,5-(diCl-MeSO(2)-B) has no effects. Furthermore, a strong induction of glial fibrillary acidic protein (GFAP) restricted to the olfactory bulb has been reported in 2,6-(diCl-MeSO(2)-B)-treated mice. To exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…We have previously reported that 2,6‐diClPh‐MeSO 2 causes long lasting, but transient, behavioural deficits in mice (Carlsson et al 2002). We proposed that these effects originated mainly from the loss of olfactory neuroepithelium, deterioration of nerve bundles, and a subsequent loss of odorant perception.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously reported that 2,6‐diClPh‐MeSO 2 causes long lasting, but transient, behavioural deficits in mice (Carlsson et al 2002). We proposed that these effects originated mainly from the loss of olfactory neuroepithelium, deterioration of nerve bundles, and a subsequent loss of odorant perception.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the low dosed groups acquisition deficits were evident at the third day in female and male rats and in male but not female mice. We have previously concluded that at least part of the increased motor activity was not dependent on olfactory mucosal deficits (Carlsson et al 2002). The dramatic differences in histopathological alterations for the two species combined with the behavioural results strengthen this conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations